RETHINKING OF RIGHTS AND PROCEDURAL COMPLEXITY IN TRANSFER OF SHARE: A REVIEW UNDER COMPANY LAW IN BANGLADESH - RAFIQUE, Zahid (Journal of Advanced Research in Law and Economics; Vol 2 No 1 (2011): JARLE Volume 1 Issue 1(3) Summer 2011, 2017)
This paper unveils the pen-picture of rights in transfer of share and the pitfalls in that regard. In order to find out the pitfalls, the Companies Act 1994 in Bangladesh has been taken as the bedrock for analysis. Also, the Listing Regulation of Dhaka Stock Exchange Limited 1996 in Bangladesh has been applied to streamline the analytical issues. Various forms in transfer of share create a problem for transferor in Bangladesh. Indeed, the provisions of the Act are manufactured in such way that it throttles the rights of transferor. The confusion over rights in joint shareholding seems to put shareholders at stake owing to the inadequate legal support. Refusal in transfer of share is lamentably more emphasized in the Act than rights and the process of transfer in provision appears favoring the refusal rather than protecting the rights. All these have been critically extrapolated with the study over the relevant English, Indian and Pakistani laws to redress the balance in transfer of share in Bangladesh.
Keywords: transfer of share, Companies Act 1994, pre-emption, refusal, director